2023
DOI: 10.1038/s41598-023-44986-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biofertilizer on heavy metal bioremediation and enzyme activities in the soil to revealing the potential for sustainable soil restoration

Mohammed Haroun,
Shifan Xie,
Waleed Awadelkareem
et al.

Abstract: Overuse of chemical fertilizer and pesticides in agricultural activity is frequently damaging to soil health and can accumulate heavy metals in the soil environment, causing harm to plants, humans, and the ecosystem. This study was done to evaluate the effectiveness of biofertilizers in reducing heavy metal levels in contaminated soil and enhancing the activity of soil enzymes that are crucial to plant growth and development. Two bacteria strains, Pseudomonas aeruginosa. and Bacillus firmus, were chosen to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
2
3
0
Order By: Relevance
“…Further, in the combined stress condition, the ARN7 + GS-BC treatment improved these enzyme activities by several fold, suggesting that the combined application significantly improved the microbial activity in the rhizosphere soil by improving soil physical, chemical, and biological properties. Similar results have been reported by Haroun et al [ 10 ], Ma et al [ 37 ], and Jabborova et al [ 44 ], where the application of PGPR and biochar improved the activity of soil enzymes under HM and drought stress conditions. Several mechanisms have been explained [ 14 , 45 , 46 ] which correlate the application of BC and/or PGPR with their effect on soil enzymes under adverse environmental condition.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Further, in the combined stress condition, the ARN7 + GS-BC treatment improved these enzyme activities by several fold, suggesting that the combined application significantly improved the microbial activity in the rhizosphere soil by improving soil physical, chemical, and biological properties. Similar results have been reported by Haroun et al [ 10 ], Ma et al [ 37 ], and Jabborova et al [ 44 ], where the application of PGPR and biochar improved the activity of soil enzymes under HM and drought stress conditions. Several mechanisms have been explained [ 14 , 45 , 46 ] which correlate the application of BC and/or PGPR with their effect on soil enzymes under adverse environmental condition.…”
Section: Resultssupporting
confidence: 90%
“…The improvement in plant growth parameters as the consequence of ARN7 treatment align with prior findings [ 18 , 20 , 27 ], indicating that the PGP metabolites of ARN7, including siderophores, IAA, exopolysaccharides, and phosphate solubilization, contribute to the enhancement of Z. mays growth under HM and drought stress. On the other hand, biochar has also been extensively investigated as a soil amendment to boost plant growth and enhance soil properties [ 10 , 13 ]. It has been shown to enhance nutrient availability, water retention capacity, and soil structure, all of which positively influence plant growth and stress resilience [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After planting Festuca arundinacea and Poa pratensis, the soil total nitrogen and available phosphorus contents showed a trend of increasing first and then decreasing with the increase in the bacterial liquid concentration, but they were all higher than those in the control treatment. The application of Bacillus cereus can increase the soil available phosphorus content, possibly due to the enhancement of soil phosphatase activity by Bacillus cereus by promoting the conversion of organic phosphorus to available phosphorus in the soil, which is similar to the findings of Haroun et al [22]. Many studies have reported that soil nutrient content is closely related to plant growth.…”
Section: Introductionsupporting
confidence: 86%
“…The concentration levels of Zn, Rb, Sr, and Y showed a significant positive correlation with the activity of CAT and PHO but a negative association with the INV activity. Haroun et al, 2023, reported a similar discovery, where the soil enzyme activities showed a significant negative correlation with heavy metals [41]. Another study by Yang et al, 2022, reported different results in correlation analysis.…”
Section: Discussionmentioning
confidence: 87%